DECISION SUPPORT SYSTEM FOR SELECTING DELIVERY SERVICES AT DEDY SEGAR USING FUZZY SAW - Tajrin Tajrin; Christoper Celinson (JIKO (Jurnal Informatika dan Komputer), 2025)
Expedition service companies play a crucial role in ensuring the smooth distribution of goods, especially for businesses involved in selling fresh products, such as Dedy Segar. However, the current delivery service selection process at Dedy Segar is still manual and lacking a structured system to evaluate, making it difficult to compare multiple important criteria such as estimated delivery time, cost, and service quality. This manual approach consumes time and effort, increases the risk of inconsistent and suboptimal decisions, and struggles to handle uncertainty in qualitative assessments. This issue poses a risk to operational efficiency and customer satisfaction, highlighting the need for a more systematic and reliable decision-making tool.. To address this problem, this study proposes a solution through the implementation of the Fuzzy Simple Additive Weighting (FSAW) method in a web-based decision support system. The FSAW method combines the advantages of fuzzy logic in handling uncertainty and the SAW method's simplicity in weighting criteria, making it suitable for evaluating subjective and imprecise data in delivery service selection. The objective of this research is to optimize the selection process of delivery services by enhancing efficiency, accuracy, and objectivity, as well as to handle uncertainty in criteria assessment. The results show that the system successfully provides recommendations based on preference values, with the highest ranking achieved by GoSend (91.00), followed by SiCepat Ekspres (87.00), Lalamove (83.50), JNE and GrabExpress (77.75), J&T Express (71.50), and TIKI and Wahana at the lowest positions. Thus, the system has proven to be effective in supporting optimal decision-making for selecting delivery services for Dedy Segar.